Hacker's Handbook: The Strategy Behind Breaking into and Defending Networks, The - Aitel, Dave (CRC Press, 2009)
The Hacker's Handbook: The Strategy Behind Breaking Into and Defending Networks, moves ahead of the pack of books about digital security by revealing the technical aspects of hacking that are least understood by network administrators. This is accomplished by analyzing subjects through a hacking/security dichotomy that details hacking maneuvers and defenses in the same context. Chapters are organized around specific technical components and administrative tasks, providing theoretical background that prepares network defenders for the always-changing and creative tools and techniques of intruders.